Barborík, Vladimír – Bystrzak, Magdalena: Modernization by criticism: Hamaliar, Chorváth, Bor, Matuška - Dušan Teplan (Slovenska Literatura)
Barborík, Vladimír – Bystrzak, Magdalena: Modernization by criticism: Hamaliar, Chorváth, Bor, Matuška